1994
DOI: 10.1128/aac.38.9.2224
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations in serum and distribution in tissue of free and liposomal amphotericin B in rats during continuous intralipid infusion

Abstract: The influences of Intralipid (IL) and 0.45% normal-saline infusions on the concentration in serum and distribution in tissue of amphotericin B (AmpB) and liposomal amphotericin B (L-AmpB) in rats were compared. In animals receiving a continuous IL infusion, concentrations of AmpB in kidneys and lungs were significantly higher, but the concentration of AmpB in serum was significantly lower in animals administered AmpB versus those given L-AmpB. In animals receiving a continuous normal-saline infusion concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…This preservation of glomerular function by lipid formulations of amphotericin B is related to several possible mechanisms. Lipid formulations of amphotericin B have a high affinity for binding to high-density lipoproteins (HDL) (46)(47)(48)(49). Binding to HDL promotes uptake in the reticuloendothelial system (RES), which has a relatively high level of expression of HDL receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This preservation of glomerular function by lipid formulations of amphotericin B is related to several possible mechanisms. Lipid formulations of amphotericin B have a high affinity for binding to high-density lipoproteins (HDL) (46)(47)(48)(49). Binding to HDL promotes uptake in the reticuloendothelial system (RES), which has a relatively high level of expression of HDL receptors.…”
Section: Discussionmentioning
confidence: 99%
“…dose of FZ (n ϭ 6) or HFZ (n ϭ 4) (1 mg of AmpB/kg) through the jugular vein. Preliminary studies have shown that an FZ dose of 1 mg/kg is sufficient to treat experimental candidiasis and yet exhibits measurable kidney toxicity (16)(17)(18)(19)(20). Following FZ and HFZ administration serial blood samples were obtained and stored in centrifuge tubes prior to and 0.083, 0.25, 0.5, 1, 2, 4, 8, 12, 24, and 48 h after the injection.…”
Section: Methodsmentioning
confidence: 99%
“…Serum and tissue samples were obtained and processed for AmpB analysis as previously described (16,(18)(19)(20). AmpB levels in serum and tissues were determined by high-pressure liquid chromatography using an external calibration curve as previously described (16,(18)(19)(20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that CSA lipoprotein distribution may be partially regulated by plasma lipoprotein cholesterol and to a lesser extent triglyceride concentrations. It further suggests that the redistribution of drug from one lipoprotein class (HDL) to another (LDL or VLDL) could be influenced by different disease states and adjunct therapies such as intralipid infusion, in which lipoprotein plasma concentrations and composition are altered 25 .…”
Section: Influence Of Lipoprotein Concentration and Composition A Secmentioning
confidence: 99%